The predictive ability of emotional creativity in motivation for adaptive innovation among university professors under COVID-19 epidemic: An international study - Čábelková, Inna; Dvořák, Marek; Smutka, Luboš; Strielkowski, Wadim; Volchik, Vyacheslav (Frontiers in Psychology, 2022)
Emotional Creativity (EC) refers to cognitive abilities and personality traits related to the originality of emotional experience and expression. Previous studies have found that the COVID-19 epidemic and restrictions imposed increased the levels of negative emotions, which obstructed adaptation. This research suggests that EC predicts the motivation for innovative adaptive behavior under the restrictions of COVID-19. In the case study of university professors, we show that EC predicts the motivation to creatively capitalize on the imposed online teaching in looking for innovative research and personal development. Methodologically we rely on the Emotional Creativity Inventory (ECI) administered to a sample of 463 university professors (41,5% men, aged 22-100. M ± SD = 45,53 ± 11,46, median 44) from the Czech Republic (N=137), Slovak Republic (N=61) and Russia (N=265). The indicators for motivation for innovative performance included motivations to use distant methods of scientific research, to look for partners for conducting scientific research in other cities or abroad, to conduct interdisciplinary research, starting distance learning to enhance qualifications, and the perception that due to online teaching there is more time for personal development. We employ a set of ordinal regression analyses controlling for age, gender, position (lecturer, researcher, manager), type of science (formal, natural, social, applied), and country. The results suggest that Emotional Creativity and its three components predict the motivation of university professors to creatively capitalize on the imposed online teaching in looking for innovative research and personal development under the conditions of COVID-19. Furthermore, our results confirmed the gender and age differences in EC. Differences in EC according to position (lecturer, researcher, manager) and type of science were not statistically significant. These results emphasize the importance of the emotional side of creativity to optimize stress-related behavior under the conditions of limited abilities to continue as usual. More space devoted to the manifestation of all aspects of emotional creativity would improve adaptation to challenging circumstances and even allow to capitalize on new opportunities. We suggest that if the personal intrinsic Emotional Creativity is high, the crises such as the COVID-19 epidemic improve adaptation and trigger creative outcomes.